Convergence and divergence in conceptualising and planning the sustainable city: an introduction. Issue 2 (15th January 2015) - Harris, Andrew; Moore, Susan
<x xml:space="preserve">Abstract</x> This special section navigates the contested terrain of the sustainable city and aims to develop new entry points for interdisciplinary dialogue and research. Six contributions from geography and planning critically engage with the simultaneous convergence of sustainable city visions and universal models of 'best practice' and the demonstrable divergence in how these visions and models are conceptualised and adopted in specific urban contexts. The papers unpack the implications of an emphasis on models and modelling of the sustainable city in relation to masterplanning, building assessment, governance, green urbanism, pedagogy and critical urban enquiry.